Growing-up just like everyone else: key components of a successful pediatric HIV disclosure intervention in Namibia. (June 2015) - Brandt, Laura; Beima-Sofie, Kristin; Hamunime, Ndapewa; Shepard, Mark; Ferris, Larissa; Ingo, Paulina; John-Stewart, Grace; O'Malley, Gabrielle
Abstract : Objectives: To facilitate replication and adaptation of pediatric HIV disclosure interventions, we identified key components of a child-friendly cartoon book used to guide Namibian caregivers and healthcare workers (HCWs) through a gradual, structured disclosure process. Design: Qualitative interviews were conducted with caregivers and HCWs from four high-volume pediatric HIV clinics in Namibia. Methods: Semi-structured in-depth interviews with 35 HCWs and 64 caregivers of HIV+ children aged 7–15 were analyzed using constant comparative and modified grounded theory analysis. Major barriers to disclosure were compared to accounts of intervention success, and themes related to key components were identified. Results: The disclosure book overcomes barriers to disclosure by reducing caregiver resistance, increasing HIV and disclosure knowledge, and providing a gradual, structured framework for disclosure. The delayed mention of HIV-specific terminology overcomes caregiver fears associated with HIV stigma, thus encouraging earlier uptake of disclosure initiation. Caregivers value the book's focus on staying healthy, keeping the body strong, and having a future 'like other kids', thus capitalizing on evidence of the positive benefits of resilience and hopefulness rather than the negative consequences of HIV. The book's concepts and images resonate with children who readily adopt the language of 'body soldiers' and 'bad guys' in describing how important it is for them to take their medicine. Discussion cues ease communication between HCWs, caregivers, and pediatric patients. Conclusion: Given the urgent need for available pediatric HIV disclosure interventions, easily implementable tools like the Namibian disclosure book should be evaluated for utility in similar settings.